Metode Perencanaan Arsitektur Perusahaan PT Ubersari Kertalangu dalam Pengelolaan Limbah B3 Medis dengan Pendekatan Manajemen Risiko - Nining Ariati; Ben Bella Al Ghiffary Faesha Putra; Ajeng Armadi Rani; Raja Amar Siregar (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
Management of medical Hazardous and Toxic (B3) waste is a major challenge in the health and environmental fields. PT Ubersari Kertalangu, as a company operating in the waste and environmental management sector, requires a structured company architecture system to support B3 medical waste management activities safely, efficiently and in accordance with regulations. This research designs a TOGAF-based corporate architecture planning method that is integrated with the ISO 31000 risk management approach. The results show that this integrative model is able to increase waste tracking accuracy, mitigate environmental and legal risks, as well as company operational efficiency..